Changes in Lifestyle Habits in Individuals with Diabetes during the COVID-19 Pandemic: The ELSA-Brasil Cohort Study - William Jones Dartora; Maria Inês Schmidt; Rosane Harter Griep; Bruce B. Duncan (COVID, 2023)
The COVID-19 pandemic and society’s response to it may have constrained the ability of those with diabetes to achieve a healthy lifestyle. We conducted a longitudinal study to assess the frequency and magnitude of sedentary habits, physical activity, sleep, alcohol consumption, weight, and smoking from July 2020 to February 2021 and compared these levels to those before the pandemic (2017–2019) in 1082 participants of the ELSA-Brasil study with known diabetes. Our results showed that inappropriate sleep duration was common (649, 68.9%) before the pandemic. Many (447, 31.1%) with this problem achieved an adequate sleep duration during the pandemic. Significant increases occurred in time in front of screens (1.3; 95%CI 0.66–2.11 h/day) and time sitting or reclining (1.4, 95%CI 0.8–2.3 h/day). Physical activity decreased (270, 95%CI 243–298 MET-min/wk). Alcohol consumption decreased without statistical significance (−19.6, 95%CI −51.1–11.9 g/w). In general, changes were similar between diabetics and non-diabetics, except that screen time in-creased less (−0.18, −0.35–−0.01 h/day) for those with diabetes. Sleep duration improved, but the frequency of sedentary habits increased, and physical activity decreased during the pandemic. Understanding changes brought on by the pandemic is essential to facilitate the implementation of quality health care for those with diabetes in moments of social stress.